An international survey examining the impact of the COVID-19 pandemic on telehealth use among mental health professionals. (April 2022) - Montoya, Madeline I.; Kogan, Cary S.; Rebello, Tahilia J.; Sadowska, Karolina; Garcia-Pacheco, José A.; Khoury, Brigitte; Kulygina, Maya; Matsumoto, Chihiro; Robles, Rebeca; Huang, Jingjing; Andrews, Howard F.; Ayuso-Mateos, José Luis; et al.
Abstract: Background: COVID-19 has profoundly affected the work of mental health professionals with many transitioning to telehealth to comply with public health measures. This large international study examined the impact of the pandemic on mental health clinicians' telehealth use. Methods: This survey study was conducted with mental health professionals, primarily psychiatrists and psychologists, registered with WHO's Global Clinical Practice Network (GCPN). 1206 clinicians from 100 countries completed the telehealth section of the online survey in one of six languages between June 4 and July 7, 2020. Participants were asked about their use, training (i.e., aspects of telehealth addressed), perceptions, and concerns. Outcomes: Since the pandemic onset, 1092 (90.5%) clinicians reported to have started or increased their telehealth services. Telephone and videoconferencing were the most common modalities. 592 (49.1%) participants indicated that they had not received any training. Clinicians with no training or training that only addressed a single aspect of telehealth practice were more likely to perceive their services as somewhat ineffective than those with training that addressed two or more aspects. Most clinicians indicated positive perceptions of effectiveness and patient satisfaction. Quality of care compared to in-person services and technical issues were the most common concerns. Findings varied by WHO region, country income level, and profession. Interpretation: Findings suggest a global practice change with providers perceiving telehealth as a viable option for mental health care. Increasing local training opportunities and efforts to address clinical and technological concerns is important for meeting ongoing demands.